Novice Writers in Asian Academia: Insights on Writing Issues - Low, Hui Min; Phoon, Hooi San; Yusof Petras; Abdul Rashid Mohamad (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Many novice researchers are encouraged to write and publish for the benefit of their careers. However, not many researchers have successfully published in the top-tier journals. Previous research on the writing outputs of researchers provided evidence that the organization of writing is among the major weaknesses which hinders this group of researchers. This paper aims to scrutinize the common issues and mistakes related to the writing practice of novice writers based on the research reports. Our investigation took place via content analysis of a database of manuscripts obtained from 23 postgraduate students, and reviewed by two experienced guest editors. The editorial remarks were analyzed and summarized using an analytical framework by Jaroongkhongdach, Todd, Keyuravong and Hall (2012) which observes five different aspects of manuscript quality. The five aspects include: justification, clarity, coherence, appropriateness and awareness. The findings indicated that many writers in this study lack awareness about research writing. The lack of this technical knowledge severely impacts the conceptualization of their written outputs. Consequently, they could not achieve the expected appropriateness in the construction of their writing in terms of justification, clarity and coherence issues of their texts. It is essential to understand the writing issues that are faced by the novice writer, so that suitable strategies could be identified to help these novice writers and potentially others to overcome their obstacles in writing.